Introduction to Business Statistics / A Computer Integrated Approach - Guynes Stephen C; Kvanli Alan H; Pavur Robert J (West Publishing Company, 1986)
Preface, A First Look at Statistics, Descriptive Graphs, Descriptive Measures, Bivariate Data, Probability Concepts, Discrete Probability Distributions, Continuous Probability Distributions, Statistical Inference and Sampling, Hypothesis Testing for the Mean and Variance of a Population, Inference Procedures for Two Populations, Estimation and Testing for Population Proportions, Analysis of Variance, Applications of the Chi-Square Statistic, Simple Linear Regression, Multiple Linear Regression, Time Series Analysis and Index Numbers, Quantitative Business Forecasting, Decision Making Under Uncertainty, Nonparametric Statistics, Appendices, Index.